(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Additive manufacturing (AM) today is a widely used and mature technology related to industry and the production of end-use components. This is a revolutionary manufacturing technology, opening great opportunities for new designs and for the production of previously impossible complexand functional products. These parts can have unique properties, outperforming other manufacturing methods and are often suitable for the most critical applications. After years of research and development of this manufacturing technique, we are now at the brink of a new era in additive manufacturing, which will include wider adoption and use of this technology, new applications, and disruptive innovations. AM especially is beneficial in the medical field, allowing for patient specific devices and implants with complex structures to be fabricated relatively cost-effectively compared to other methods. Special advanced implants combining different material properties allow the implant to be more bio-compatible and increase the lifespan. The rising costs of health care are attributed to an increasing number of medical procedures with great complexity and costly instrumentation. Advanced innovative materials and devices must be developed to reduce the time, economic cost, and physical pain, hence the urgent need for this life saving research work by using AM techniques. Igor Yadroitsev is a Research Chair in Medical product development through Additive Manufacturing at the Central University of Technology launched by National Research Foundation of South Africa in 2015. He has been involved in the additive manufacturing field with emphasis on laser powder bed fusion in Vitebsk Institution of Technical Acoustics (Belarus) since 1995, when this technology was in its infancy. He continued his research in this area at the National School of Engineering (Saint-Etienne, France) during 2005-2013. Since 2014, Igor Yadroitsev is a professor at the Faculty of Engineering, Built Environment and Information Technology, Central University of Technology (CUT), Free State, Republic of South Africa. His research interests include applied optics and laser technologies: additive manufacturing, laser powder bed fusion of metals and plastics, laser processing, materials science.